Digital Transformation in African Parliaments - Mosienyane, Tefo (CLEAR-AA, 2021)
This learning note draws on lessons from the piloting of the African Parliamentary Oversight Tool developed by the Centre for Learning on Evaluation and Results – Anglophone Africa’s (CLEAR-AA) in two African parliaments. It further outlines lessons and recommendations to guide practitioners in implementing successful digital transformation initiatives in African Parliaments. The African POT is an online research management tool that emanates from CLEAR-AA’s commitment to support and improve evidence generation and use that furthers better decision making. The African POT is a digital intervention project that undertakes digital transformation in evidence generation, use and culture in African Parliaments. This happens through a mobile application that integrates the evidence process, from the demand side by the MP. Evidence is then synthetized by parliamentary researchers to facilitate MPs use of evidence This platform digitalises some of the existing processes, but in the long term is designed to bring about organizational, cultural and process changes that allow for a culture of evidence-based decision making to flourish. The key issues of consideration in piloting the African POT involved data governance, security and vulnerability, implementation challenges related to staff capacity, technical language and the type of commitments required from practitioners and parliaments in implementing the tool.